An Empirical Investigation of Health Practitioners Technology Adoption: The Mediating Role of Electronic Health. Issue 12 (9th September 2020) - Arkorful, Vincent Ekow; Shuliang, Zhao; Muhideen, Sayibu; Basiru, Ibrahim; Hammond, Anastasia
ABSTRACT: Health technology innovation integration is rapidly growing in global health-care settings. However, research on factors driving technology adoption intention is limited. On this note, it has become important to investigate and understand the complex factors underpinning practitioners' technology adoption intentions. Drawing on the Technology Acceptance Model and The Institutional Theory, we propose a model to empirically investigate technology adoption and its potency in driving universal health coverage, mediated by electronic health technology. We used data collected from 416 health sector practitioners to empirically test the model. Using the Structural Equation Modeling technique, the study found that perceived ease of use and relevant technology infrastructure all have significant positive relationship with universal health coverage. However, perceived usefulness, management support and adequate practitioner training were found to have negative relationship with universal health coverage. The results further revealed that perceived-ease-of-use, perceived usefulness, management support, adequate practitioner training and relevant technology infrastructure also have positive relationship with electronic health technology. Moreover, electronic health technology as a mediator was also found to have significant relationship with universal health coverage. The implications of the findings are discussed and suggestions for future research are subsequently highlighted.